Contemporary practice and resource availability for genetic testing in paediatric hypertrophic cardiomyopathy - Sandmann, Christoph; Klaassen, Sabine; Kaski, Juan Pablo; Norrish, Gabrielle (Journal of medical genetics, 2025)
The 2023 European Society of Cardiology (ESC) Guideline for the Management of Cardiomyopathies and the 2024 American Heart Association (AHA)/American College of Cardiology (ACC)/AMSSM/HRS/PACES/SCMR Guideline for the Management of Hypertrophic Cardiomyopathy (HCM)1 2 now recommend routine genetic testing for all children fulfilling diagnostic criteria for HCM. Guideline recommendations on phenotype description and the use of cardiac MR imaging have resulted in a change in clinical practice, but whether the same applies to genetic testing in childhood HCM is unknown.3 To understand current resource availability and clinical genetic testing practice, we performed a survey of centres caring for children with HCM within the International Paediatric Hypertrophic Cardiomyopathy Consortium (IPHCC), a large geographically diverse consortium of expert paediatric cardiomyopathy providers.4 - - An electronic survey was distributed to all members of the IPHCC (number of centres=42) between May 2024 and August 2024, of whom 34 centres from 14 countries (figure 1A) responded (online supplemental table 1). 20 centres (59%) were colocated with adult services and the number of HCM patients seen annually varied (<50 n=15 (44%), 50-100 n=10 (29%), >100 n=6 (18%), no information n=3 (9%)) (figure 1B). A third of centres reported an increase in the frequency of genetic testing (n=11, 32%) following changes in guideline recommendations1 2 (figure 1C). As a result, the majority (n=32, 94%) routinely offer genetic testing to all patients meeting diagnostic criteria for HCM (figure 1D). The provider of genetic testing varied across centres (geneticist n=16 (47%), cardiologist n=5 (15%), geneticist and cardiologist n=13 (38%) (figure 1E) and only two-thirds (n=20, 59%) routinely offer pretest genetic counselling (figure 1F). For most centres, genetic testing is funded by the health service or government (n=29, 78%), with a smaller number funded by health insurance (n=3, 8%) or the patient themselves (n=5, 15%).
Gesehen am 04.11.2025